The Methylation of Clock Genes in Perinatal Depression: Which Role for Oxytocin? - Iodice, Simona; Di Paolo, Martina; Barkin, Jennifer Lynn; Tarantini, Letizia; Grassi, Silvia; Redaelli, Marta; Serati, Marta; Favalli, Virginia; Cirella, Luisa; Bollati, Valentina; Buoli, Massimiliano (Frontiers in Psychiatry, 2021)
Background: Perinatal Depression (PD) is a widespread disabling condition that is hypothesized to be associated with abnormalities in circadian rhythms and neuropeptide release including oxytocin (OXT). Methods: Fourty-four pregnant women (28 with PD, and 16 controls) were evaluated through the Edinburgh Postnatal Depression Scale (EPDS), the State/Trait Anxiety Inventory Form Y (STAI-Y), and the Prenatal Attachment Inventory (PAI). A blood sample was collected from all participants, and OXT plasma levels, DNA methylation of clock genes, FOXp3, HERV-W were measured. Linear regression analyses were performed to assess the effect of oxytocin on the methylation of selected genes. Continuous ordinal regression models was further applied to see if the score of rating scales was associated to gene methylation, adjusting for oxytocin-methylation interaction. Results: OXT plasma levels were positively associated with CRY1 methylation. Women with higher OXT plasma levels showed an association between higher degree of CRY2 methylation and lower EPDS (OR= 0.21; P= 0.043) and STAI-S scores (OR= 6.96; P= 0.019). Finally, with high OXT levels, hypermethylation of CRY1 was associated to higher scores on the PAI (OR= 2.74; P= 0.029) while higher methylation of HERV-W related to lower PAI scores (OR= 0.273; P= 0.019). Conclusions: Our results suggest a possible protective role played by oxytocin in the development of PD by promoting a favorable methylation profile characterized by reduced expression of CRY1 and CRY2. Moreover oxytocin strengthens the association between maternal prenatal attachment with a favorable pattern of methylation of clock genes and HERV-W, which is essential for pregnancy outcomes.